Early Growth Hormone Intervention Improves Glucose Metabolism in Adult Rats Born Small for Gestational Age - Wang, Yingmin; Zhu, Weifen; Chen, Lianhui; Liang, Li (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Small for gestational age (SGA) due to intrauterine malnourishment is closely related to metabolic syndrome and type 2 diabetes mellitus. Growth Hormone (GH) treatment has been demonstrated to influence metabolic parameters and islet function of SGA individuals. The present study demonstrates the effects of early GH treatment on glucose tolerance and expression of pancreatic duodenal homeobox 1 (Pdx1) of SGA rats during adulthood.Methods SGA rat model was induced by restricting food intake during pregnancy. GH or normal saline was administered during postnatal days 21–35 of SGA rats and appropriate for gestational age (AGA) rats, respectively.Results In early adulthood (postnatal day 70), as compared to AGA rats, SGA rats showed: (1) decreased body weight; (2) increased postprandial blood glucose; and (3) down-regulated Pdx1 with increased histone deacetylase (HDAC) and down-regulated histone H3-lysine 4 methyltransferase SET7/9. Exogenous GH administration led to a restoration of body weight and normalized glucose tolerance due to an enhanced Pdx1 expression, accompanied by decreased HDAC and up-regulated SET7/9 in SGA rats in early adulthood.Conclusion Our results demonstrate positive effects on glucose metabolism by an early and short GH treatment in SGA adulthood.
Keywords: small for gestational age; pdx1; growth hormone